Quality and Shelf-Life Evaluation of Packaged Biscuits Marketed in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2012)
Five different brands of locally produced biscuits and five brands of foreign biscuits were collected from the market. All these biscuits were  stored at ambient condition (30 ºC, and 60 % RH) for 3 months. The changes in water activity, moisture and their consequences on sensory  qualities like texture, color, flavor and overall acceptance were investigated in every month. Test of packaging materials were also carried  out for each brand of packed biscuits. Moisture and water activity values have been increased with time for all the samples whereas  sensory scores decreased. However, all the foreign and local biscuit samples were found acceptable under the study period but only one  local biscuit was found unsalableDOI: http://dx.doi.org/10.3329/bjsir.v47i1.10717 Bangladesh J. Sci. Ind. Res. 47(1), 29-42, 2012